Pelo direito de qualquer um fazer cidade : construção subjetiva dos espaços urbanos - Vilas Novas, Bruno Bowen (2015)
This document focuses on investigating the theories and practices of urban production in the contemporary city, approaching the actions and the spatialized micro narratives as alternatives or resistances, contrasting them to the hegemonic macro-political